2022
DOI: 10.48550/arxiv.2202.02437
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact forces of water drops falling on superhydrophobic surfaces

Bin Zhang,
Vatsal Sanjay,
Songlin Shi
et al.

Abstract: A falling liquid drop, after impact on a rigid substrate, deforms and spreads, owing to the normal reaction force. Subsequently, if the substrate is non-wetting, the drop retracts and then jumps off. As we show here, not only is the impact itself associated with a distinct peak in the temporal evolution of the normal force, but also the jump-off, which was hitherto unknown. We characterize both peaks and elucidate how they relate to the different stages of the drop impact process. The time at which the second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…This is caused by the rapid retraction and bounce of the droplet on the superhydrophobic wall during the impact process. In another study (Zhang et al, 2022), the impact force of a water droplet impacting on superhydrophobic walls was also investigated. Results indicated that the secondary peak of the impact force can occur even at low impact velocities, and its magnitude may even be larger than that of the first peak.…”
Section: Introductionmentioning
confidence: 99%
“…This is caused by the rapid retraction and bounce of the droplet on the superhydrophobic wall during the impact process. In another study (Zhang et al, 2022), the impact force of a water droplet impacting on superhydrophobic walls was also investigated. Results indicated that the secondary peak of the impact force can occur even at low impact velocities, and its magnitude may even be larger than that of the first peak.…”
Section: Introductionmentioning
confidence: 99%
“…It will be interesting to probe such a regime in future work. [5,70,158]. This downward jet can puncture the air film and lead to coalescence during the drop retraction.…”
Section: Discussionmentioning
confidence: 99%